Exploring Oral Presentation Performance: Level of Mastery and Common Problems of EFL Students from Selected University - Sahan, Anselmus; Abi, Benyamin Kau; Wisrance , Maria W.; Seran, Yanuarius (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
This study aims to explore the EFL students’ performance in oral presentation by categorize their level of mastery, and to reveal if there are any common problems during the performance. This descriptive quantitative study purposively invited 24 students as the samples from the third semester of English Study Program at Timor University. The data were based on students’ performance on 10 selected texts which recorded to measure their oral presentation after an internal workshop. The analysis and the scoring were based on Harris’ (1969) five components in scoring speaking and with Brown’s (2004) six oral proficiency scoring categories. However, this study focusing only on the pronunciation and fluency categories to be in line with the scoring rubric of competence in the 2021 Academic Regulation of Timor University. The results showed that the students have mastered the oral presentation because their average score is 82 based their right answer is 144/150. This average scores then analysed using the Academic Regulation of Timor University (2021) showing the majority of the students is categorized excellent (19 out of 26 students). Nevertheless, two major problems in common this study manage to reveals were mispronounced/wrong pronunciation (13%) and lack of fluency (5%). The result implies that these two common problems should be put in attention during the process of learning oral performance i.e., English presentation in public. Further studies are suggested to investigate the impact of practice in improving students’ oral presentations through specific workshop.